DESIGN OF FINANCIAL RECORDING SYSTEM USING WATERFALL METHOD AT ARTHO FURNITURE STORE - Dwi Purnomo, Raka; Ardi Wijaya, Setiawan; Mardiyanto, Silvia (JATI (Jurnal Mahasiswa Teknik Informatika), 2025)
This research aims to develop a financial recording system for Artho Furniture using the Waterfall method based on the needs that have been identified. The results show that the system successfully automates transaction recording, reduces manual errors by 80%, and produces clear and accurate financial reports. The test results showed improved efficiency, transparency, and accountability in financial management, enabling shop owners to make better business decisions. With accurate and timely financial data, operational activities run more effectively. The system was developed using PHP and MySQL, with a user-friendly interface to facilitate users in daily operations.